Relationships between Structure, Composition, and Dynamics of the Pristine Northern Boreal Forest and Air Temperature, Precipitation, and Soil Texture in Quebec (Canada) - Louis Duchesne; Rock Ouimet (International Journal of Forestry Research)
This study reports on the contemporary structure, composition, and dynamics of the pristine northern boreal forest in Quebec, Canada, associated with air temperature, precipitation, and soil texture, using 147 permanent sample plots located at the limit of continuous forest in Quebec. The results show that tree species composition of stands is associated with stand age, soil texture, air temperature, and precipitation regime. After establishment of the pioneer cohort, the postsuccessional stand dynamics differed among temperature and precipitation regimes, probably because of their influence on tree growth. Our results support the hypothesis that shifts in forest composition related to stand dynamics and the subsequent senescing phase associated with the old growth stage generally occur sooner and proceed faster on more fertile sites due to quicker growth and the subsequent earlier mortality of pioneer species. This study suggests that climate warming should accelerate the successional dynamics of these ecosystems through its positive influence on tree growth.